1985
DOI: 10.3133/ofr85380
|View full text |Cite
|
Sign up to set email alerts
|

Beaufort Sea coastal erosion, shoreline evolution, and sediment flux

Abstract: Within the conterminous United States, the Gulf of Mexico coast has the highest erosion rates. The Texas coast, in many respects similar to that of the Beaufort Sea, retreats on average 1.2 m/yr, or about half the Beaufort Sea average. Since coastal erosion in arctic regions is restricted to three summer months when waves and coastal currents are active, erosion rates there must be multiplied by a factor of four for a meaningful comparison with the Texas coast, which experiences waves and currents year round. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 43 publications
1
46
1
Order By: Relevance
“…Recent studies have documented coastal erosion rates as high as 20 m y 21 along segments of the Beaufort Sea coastline using remote sensing and repeat mapping of coastal position (Reimnitz et al, 1985;Jorgenson and Brown, 2005;Mars and Houseknecht, 2007;Jones et al, 2008Jones et al, , 2009. Since all of this erosion must occur during the short ice-free season, these documented rates indicate that summertime erosion is rapid enough to be directly observable using time-lapse photography.…”
Section: Study Sitementioning
confidence: 99%
“…Recent studies have documented coastal erosion rates as high as 20 m y 21 along segments of the Beaufort Sea coastline using remote sensing and repeat mapping of coastal position (Reimnitz et al, 1985;Jorgenson and Brown, 2005;Mars and Houseknecht, 2007;Jones et al, 2008Jones et al, , 2009. Since all of this erosion must occur during the short ice-free season, these documented rates indicate that summertime erosion is rapid enough to be directly observable using time-lapse photography.…”
Section: Study Sitementioning
confidence: 99%
“…Barnhart et al (2014) report that the mean erosion rate over a 7 km stretch of the central-west Beaufort Sea coast just east of Drew Point was 15 m yr −1 (2008)(2009)(2010)(2011) and 19 m yr −1 (2011)(2012). Early work in the region documented coastal retreat rates that locally reached 18 m yr −1 (during the period 1950-1980) (Reimnitz et al, 1985(Reimnitz et al, , 1988. More re- cently Wobus et al (2011) reported local rates that reached 30 m yr −1 in the summer of 2008.…”
Section: Arctic Climate and Arctic Coastsmentioning
confidence: 99%
“…The numbers represent features and sites discussed in the text and listed in Table 1; these include coastal features, known cultural/historical sites, and modern infrastructure. The sectors were defined by Reimnitz et al (1985).…”
Section: Study Area and Backgroundmentioning
confidence: 99%
“…Long-term rates of erosion along the Alaska Beaufort Sea coast have averaged 2.5 m a -1 , with higher rates occurring along the western stretches (3.0 to 5.4 m a -1 ) and lower rates occurring along the eastern stretches (1.0 to 1.4 m a -1 ) (Lewellen, 1970;Reimnitz et al, 1985;Barnes et al, 1992;Brown et al, 2003;Jorgenson et al, 2003;Manley, 2004). By comparison, recent long-term rates of erosion along the Canadian Beaufort Sea coast have averaged 1.0 to 2.0 m a -1 (Mackay, 1986;Harper, 1990;Solomon, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation